Activation of the Nlrp1b Inflammasome by Reduction of Cytosolic ATP - Liao, Kuo-Chieh (American Society for Microbiology, 2013)
The efficacy of the innate immune system depends on its ability to mount an appropriate response to diverse infections and damaging agents. Key components of this system are pattern recognition receptors that detect pathogen-associated and damage-associated molecular patterns (PAMPs and DAMPs). Nlrp1b is a pattern recognition receptor that forms a caspase-1 activation platform, known as an inflammasome, upon sensing the proteolytic activity of anthrax lethal toxin. The activation of caspase-1 leads to the release of proinflammatory cytokines that aid in the clearance of the anthrax infection. Here, we demonstrate that Nlrp1b also becomes activated in cells that are subjected to energy stress caused by metabolic inhibitors or by nutrient deprivation. Glucose starvation and hypoxia were used to correlate the level of cytosolic ATP to the degree of inflammasome activation. Because lowering the ratio of cytosolic ATP to AMP activates the main cellular energy sensor, AMP-activated protein kinase (AMPK), we assessed whether AMPK promoted inflammasome activity by using a combination of small interfering RNA (siRNA) and transfection of a dominant negative AMPK subunit. We found that AMPK promoted inflammasome activity, but activation of AMPK in the absence of ATP depletion was not sufficient for caspase-1-mediated pro-interleukin 1β (pro-IL-1β) processing. Finally, we found that mutation of the ATP-binding motif of Nlrp1b caused constitutive activation, suggesting that ATP might inhibit the Nlrp1b inflammasome instead of being required for its assembly.